The fate and transport of some commonly used pesticides in the Konya plain - Ongar, Yağmur. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2022., 2022)
By protecting the agricultural products, pesticides are substances that are widely used worldwide to increase crop yields. Although pesticides can have beneficial effects on crop production, these chemicals have various adverse effects on human health, other living and environmental systems. By virtue of the aforementioned reasons, it is a necessity to understand the fate, transport and interactions of the pesticides in the natural systems. In this study, in order to investigate the fate and transport of two pesticides widely used in the Konya Plain (2,4-dichlorophenoxyacetic acid and fenoxaprop-p ethyl), a series of batch sorption and column transport experiments were conducted. Soil samples collected from the Konya Plain were screened for a wide range of pesticides using liquid chromatography coupled with tandem mass spectroscopy (LC-MS/MS). Extraction of the pesticides from the soil samples was performed using “quick, easy, cheap, effective, rugged, and safe” QuEChERS method. Batch tests were conducted using selected soil samples to investigate the sorption potential of the target pesticides. Sorption kinetics as well as sorption isotherms were developed for the two pesticides. Column tests were conducted to evaluate the mobility potential of the target pesticides. Calibration curves with linear regression coefficients (R2 ) greater than 0.990, were used for the estimation of distribution coefficients (Kd). The 24h Kd value of the Fenox was calculated as 297.4 mL g-1. There was no significant Kd value calculated for 2,4-D. Overall, the experiments demonstrated that the transport potential of 2,4-D is high while Fenox mobility is limited due to its high sorption.
Keywords: Pesticides -- Konya.; Pesticides -- Environmental aspects.